PHOSPHATE AND NITRATE REMOVAL FROM DRINKING WATER SOURCES USING ACRYLAMIDE-FERRIHYDRITE GEL - Barlah Rumhayati; Chasan Bisri; Heni Kusumawati; Faridah Yasmin (Universitas Gadjah Mada, 2012)
Phosphate and nitrate ions removal from drinking water has been conducted using acrylamide-ferrihydrite gel. The gel was prepared by mixing the ferrihydrite paste and acrylamide gel solution followed by casting at temperature 42-46 °C for at least one hour. The effect of pH and concentration of phosphate and nitrates to the percent of removal were investigated. Desorption efficiency was also investigated using sulphuric acid at various concentration. As a result, phosphate and nitrate could be removed optimally at pH 5. The solution concentration of nitrate for optimum removal was 10 mg/L NO3-, whilst phosphate could be removed optimally at concentration of 0.3 mg/L PO43-. The analytes could be desorbed from the gel using H2SO4 0.3 M. In application, phosphate and nitrate in the drinking water sources could be removed up to 70%.